Origin and development of western education in Gombe Emirate, Nigeria - Arawa, Abubakar A.; Ahmed, Bappah (Kashere Journal of Education, 2023)
Education whether in its traditional or modern form which is term western education is a tool for socio-economic and political development of any society. Western education was therefore, introduced in Gombe Emirate, in the present Gombe State in 1925, by the colonial administration to serve the efficient running of the colonial government. Since the evolvement of western education in the emirate, and the exit of colonialism, it has thrived on, the government and other stakeholders have continued to invest in western education in the emirate. The puzzle that arises is that to what extent has the education transformed over time. Is it still stuck to the colonial thought or ideology of it serving colonial interest? The problems this paper intent to address lies in the fact that it explores to find out if the colonial legacy of western education has transformed over time: from when it evolved up to 1960 in Gombe emirate, the drivers of such transformations, the impacts of the transformation and the challenges faced by the transformation processes. The paper found that the colonial legacy has indeed transformed and created impacts beyond the colonial targets and thought. It as well established that the transformation process has been impinged by some of the factors such as the bookish nature of the education and lack of practical orientation etc. Practical vocational skills and entrepreneurial knowledge needs to be emphasis in the educational system. The information and data for analysis in the reconstruction of this paper was obtained from primary sources including archival materials and secondary sources such as published and unpublished materials